Potensi Cendawan Endofit sebagai Pengendali Hayati Penyakit Busuk Pangkal Batang (Phytophthora capsici) pada Bibit Cabai - Evan Purnama Ramdan; Efi Toding Tondok; Suryo Wiyono; Sri Hendrastuti Hidayat; Widodo Widodo (Jurnal Fitopatologi Indonesia, 2017)
Stem rot disease caused by Phytophthora capsici is an important disease on chilli. Eight endophytic fungi that had been isolated and screened based on pathogenecity test were further tested for their potential as the biological control agent of the stem rot disease of chilli. The endophytic fungi suspension was applied twice during the trial. The first application was on 100 seed lot, by soaking them in 100 mL of suspension. The second application was on the 3 weeks-old chili seedlings by drenching them with 10 mL suspension per plant. The concentration of endophytic fungi  in the suspension was 2.8 × 106 cfu mL-1. The disease intensity and AUDPC value were measured for 4 weeks after the pathogen inoculation. The growth inhibition test of P. capsici  was performed in vitro and the colonization abilities of endophytic fungi were observed at 4 weeks-old chilli seedlings. Eight endophytic fungi  inhibited the growth of the P. capsici, and two of those isolates namely Penicillium strain MAG1 and Penicillium strain PAB2 showed antibiosis mechanism. Endophytic fungi has the ability more to colonize at the root (26–60%) than in the stem (20–40%). Fusarium strain MAGR1 has the highest level of endophytic colonization i.e. 60% compared to others.  Based on in vivo assay, six endophytic fungi isolates, i.e. Fusarium strain MAGR1, Penicillium strain MAG1, Penicillium strain PAB2, sterile hyphae HAJ1, sterile hyphae HAJ2, and  sterile hyphae PBG7, showed the potency to control stem rot disease with inhibition level of 25.5–35.5%